كفــاءة أجهــزة الرقــابة المالــية والإداريــة الحكــومية في مراقــبة ومتــابعة حسابات المؤسسات الاجتماعية - معتوقد. عبدالحميد إبراهيم; عبد الدائمد. عبدالمجيد محمد (Aljameai, 2022)
الملخص: تهدف هذه الدراسة إلى التعرف على الخدمات التي تقدمها المؤسسات الاجتماعية بصفة عامة ، ونظم الرقابة الداخلية المتبعة في النوادي الرياضية بصفة خاصة، بالإضافة إلى أجهزة الرقابة الحكومية ودورها في متابعة ورقابة النوادي الرياضية في مدينة طرابلس. توصلت هذه الدراسة إلى النتائج التالية: لا يوجد مراقبين ماليين بهذه المؤسسات؛ يوجد بها إلى حد ما مراجعين داخليين؛ عدد الموظفين قليل وأغلبهم متطوعين؛ نتيجة لقلة الموارد المالية الممنوحة من وزارة الشباب والرياضة للنوادي الرياضية من جهة وإهمال دور أجهزة الرقابة المالية الحكومية من جهة أخرى، فأنه لا يوجد نظام محاسبي متكامل في هيكلية أغلب النوادي الرياضية؛ غياب سياسات الحوافز والتدريب للموظفين الأمر الذي ساهم في ضعف نظام الرقابة الداخلية لا سيما (الرقابة السابقة) والمتمثلة في عدم وجود دورات مستندية وسجلات ودفاتر ودليل حسابات ، وكذلك (الرقابة المرافقة) والمتمثلة في عدم إتمام المعاملات المالية بصورة سليمة ، وغيرها من مقومات النظام المحاسبي عموماً. Abstract:: This study aims to identify the services provided by social institutions in general, and the internal control systems used in sports clubs in particular, in addition to government control bodies and their role in following up and control of sports clubs in Tripoli. The study reached the following results: There are no financial Controller in these institutions; To some extent, it has some internal auditors; The number of employees is small and most of them are volunteers; As a result of the lack of financial resources granted by the Ministry of Youth and Sports to sports clubs on one hand and the neglect of the role of government financial control bodies on the other hand, there is no integrated accounting system in the structures of most sports clubs; The absence of policies for incentives and training for employees, which contributed to the weakness of the internal control system, especially earlier control, because of the absence of documentary cycles, records, books and chart of accounts as well as the accompanying control represented in the lack of proper completion of financial transactions, and other makings of the accounting system in general.